A Study of Non-Cooperation Movement History: Causes, Result and Importance: The Intersection of Political and Religious Movements in the Non-Cooperation Movement (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The developing outrage against the British administer prompted the starting of the Khilafat and Non-Cooperation development. Turkey had battled against Britain in the First World War. Turkey, which was one of the vanquished nations, endured treacheries on account of Britain. In 1919, a development was composed under the authority of Mohammad Ali and Shaukat Ali (prevalently known as Ali siblings), Abul Kalam Azad, Hasrat Mohani and others to drive the Britain government to fix these shameful acts. The Khilafat board of trustees which was set up to direct this development was joined by Gandhi. The sultan of Turkey was additionally viewed as the Caliph or Khalifa, the religious leader of the Muslims. Accordingly the development over the subject of the shamefulness done to Turkey was known as the khilafat development. It gave a call for non-collaboration. The development on the Khilafat question soon converged with the development against the restraint in Punjab and for swaraj.